# (n/n-3)+2=(3/2n-1)

## Simple and best practice solution for (n/n-3)+2=(3/2n-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for (n/n-3)+2=(3/2n-1) equation:

(n/n-3)+2=(3/2n-1)
We move all terms to the left:
(n/n-3)+2-((3/2n-1))=0

Domain of the equation: n-3)!=0
n∈R

Domain of the equation: 2n-1))!=0
n∈R

We get rid of parentheses
n/n-((3/2n-1))-3+2=0
Fractions to decimals
-((3/2n-1))-3+2+1=0
We multiply all the terms by the denominator
-((3-3*2n-1))+2*2n-1))+1*2n-1))=0

We calculate terms in parentheses: -((3-3*2n-1)), so:
(3-3*2n-1)
We add all the numbers together, and all the variables
(-3*2n+2)
We get rid of parentheses
-3*2n+2
Wy multiply elements
-6n+2
Back to the equation:
-(-6n+2)

Wy multiply elements
-(-6n+2)+4n-1))+1*2n-1))=0
We get rid of parentheses
6n+4n-1))+1*2n-1))-2=0
We add all the numbers together, and all the variables
10n-1))+1*2n-1))-2=0

`